Memahami Motif Melakukan Binge-Watching pada Mahasiswa Perempuan - Izzatul Ummah; Shafira Putri Charnita; Silvi Rahma Putri Riyani; Nisrina Fadhila; Siti Athaya Khansa; Irin Riamanda (Syiah Kuala Psychology Journal, 2024)
Binge-watching is the activity of watching multiple episodes of a TV series or drama consecutively without breaks. This activity leads individuals to spend long periods in front of screens, and research has shown that women tend to engage in it more frequently. This study aims to understand the main motives behind binge-watching behavior among female university students. A qualitative research approach using qualitative descriptive methods was employed through interviews with five respondents aged 18-22, who are female students at a university in Aceh. The results revealed several primary motives for binge-watching among female students. While each subject had different motives, stress relief and seeking entertainment were the main reasons for binge-watching. These findings provide a deeper understanding of binge-watching behavior among female students and highlight the need for further research on the impact of binge-watching on other aspects such as mental health and interpersonalrelationships.Binge-watching merupakan aktivitas menonton beberapa episode serial TV atau drama berturut-turut tanpa jeda. Aktivitas ini membuat seseorang berada di depan layar dalam waktu yang lama, dan penelitian mengungkapkan bahwa perempuan lebih sering melakukannya. Penelitian ini bertujuan untuk memahami motif utama di balik perilaku binge-watching pada mahasiswa perempuan. Pendekatan penelitian yang digunakan adalah kualitatif dengan metode kualitatif deskriptif melalui proses wawancara kepada lima responden berusia 18-22 tahun yang merupakan mahasiswa perempuan di sebuah universitas di Aceh. Hasil penelitian menunjukkan bahwa terdapat beberapa motif utama mahasiswa perempuan melakukan binge-watching. Setiap subjek memiliki perbedaan motif, namun meredakan stres dan mencari hiburan menjadi motif utama mahasiswa perempuan melakukan binge-watching. Temuan ini dapat memperdalam pemahaman tentang perilaku binge-watching pada mahasiswa perempuan dan perlu dilakukan penelitian lebih lanjut mengenai dampak binge-watching pada aspek lain, seperti kondisi kesehatan mental dan hubungan interpersonal.